ASSOCIATION OF VITAL SIGNS AND PAIN SCORE IN EMERGENCY DEPARTMENT - WAHEED, A; IFTIKHAR, H; WAHEED, A; HUMAIRA, .; KHAN, AS (Biological and Clinical Sciences Research Journal, 2024)
Accurate pain assessment is essential in emergency settings to ensure timely and effective management. Although self-reported pain scores are commonly used, healthcare providers often rely on vital signs, such as heart rate, respiratory rate, blood pressure, and temperature, as additional indicators of pain. However, the reliability of these vital signs in predicting pain remains unclear. Objective: To investigate the relationship between vital signs (heart rate, respiratory rate, blood pressure, and temperature) and self-reported pain scores in adult emergency department (ED) patients, evaluating the reliability of vital signs as pain indicators. This prospective obseMethods: rvational study was conducted over one month in the emergency department of a tertiary care hospital in Islamabad, Pakistan. A total of 201 adult patients (aged ≥16 years) presenting with pain were included, while those with altered mental status, non-painful complaints, or terminal illness were excluded. Upon arrival, vital signs and self-reported pain scores were documented using a standardized form. Pearson correlation coefficients were used to assess the association between each vital sign and pain score. Subgroup analyses further examined differences by demographics, pain etiology (traumatic vs. non-traumatic), and pain severity. Results: No significant correlation was observed between vital signs and pain scores (p < 0.001), suggesting that vital signs are not reliable indicators of pain intensity in ED patients. Conclusion: Vital signs, such as heart rate, respiratory rate, and blood pressure, show limited reliability as indicators of pain. Self-reported pain scores should be prioritized in pain assessment to ensure timely and accurate pain management, potentially improving patient satisfaction. Further multi-centre research is recommended to explore variations in pain relief strategies based on pain type and demographics.